Evaluation of cell responses toward adhesives with different photoinitiating systems - Van Landuyt, Kirsten L.; Krifka, Stephanie; Hiller, Karl-Anton; Bolay, Carola; Waha, Claudia; Van Meerbeek, Bart; Schmalz, Gottfried; Schweikl, Helmut (Dental materials, 2015)
The photoinitiator diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) is more reactive than a camphorquinone/amine (CQ) system, and TPO-based adhesives obtained a higher degree of conversion (DC) with fewer leached monomers. The hypothesis tested here is that a TPO-based adhesive is less toxic than a CQ-based adhesive. A CQ-based adhesive (SBU-CQ) (Scotchbond Universal, 3M ESPE) and its experimental counterpart with TPO (SBU-TPO) were tested for cytotoxicity in human pulp-derived cells (tHPC). Oxidative stress was analyzed by the generation of reactive oxygen species (ROS) and by the expression of antioxidant enzymes. A dentin barrier test (DBT) was used to evaluate cell viability in simulated clinical circumstances. Unpolymerized SBU-TPO was significantly more toxic than SBU-CQ after a 24h exposure, and TPO alone (EC50=0.06mM) was more cytotoxic than CQ (EC50=0.88mM), EDMAB (EC50=0.68mM) or CQ/EDMAB (EC50=0.50mM). Cultures preincubated with BSO (l-buthionine sulfoximine), an inhibitor of glutathione synthesis, indicated a minor role of glutathione in cytotoxic responses toward the adhesives. Although the generation of ROS was not detected, a differential expression of enzymatic antioxidants revealed that cells exposed to unpolymerized SBU-TPO or SBU-CQ are subject to oxidative stress. Polymerized SBU-TPO was more cytotoxic than SBU-CQ under specific experimental conditions only, but no cytotoxicity was detected in a DBT with a 200μm dentin barrier. Not only DC and monomer-release determine the biocompatibility of adhesives, but also the cytotoxicity of the (photo-)initiator should be taken into account. Addition of TPO rendered a universal adhesive more toxic compared to CQ; however, this effect could be annulled by a thin dentin barrier.